(untitled) (Research, Society and Development, 2022)
Objective: The present study aimed to investigate the relationships between treatment adherence and quality of life in people with hemophilia that have been published in the scientific literature. Methods: This is an integrative review carried out in the Virtual Health Library, PUBMED and COCHRANE databases, including articles published from January 2012 to May 2022. Results: Based on the inclusion and exclusion criteria, we selected 05 articles. Articles that studied children and adults with hemophilia predominated (75%). All articles presented level of evidence VI (100%). The number of participants involved in the studies ranged from 24 to 117. Two articles addressed only Hemophilia A, four addressed hemophilia A and B concomitantly and in one the sample of hemophiliacs B was insignificant, raising the analysis only of hemophiliacs A. Final considerations: All articles found a direct relationship between treatment adherence and quality of life.